Facilitating Students’ Multimodal Competence Development in Technology-Supported Speaking Class Through Multiliteracies Pedagogy - Hidayah, Jumatul; Prihantoro, Prihantoro; Apriani, Eka; Polisda, Yen; Arnanda, Farenz Sukma; Oktavia, Nazlah (UNIB Press, 2025)
This study aimed to investigate the implementation of multiliteracies pedagogy in a technology-supported speaking class to enhance students' multimodal competence. Based on the fact that the State Islamic Institute Curup's (IAIN Curup) English Language Education Department's multimodal literacy skills are being hampered by the traditional literacy paradigm, this case study were held by involving 20 fifth-semester undergraduate students. Data were collected through classroom observations, semi-structured interviews, online questionnaires, and variety of student assignments, such as digital posters and videos. The data were analyzed qualitatively using Creswell's Data Analysis Procedures, involving iterative coding to identify themes and patterns. The results showed that students' ability to produce and evaluate multimodal texts was enhanced by the multiliteracies pedagogy. According to the data collection and rubric created to evaluate their tasks, students showed improved abilities to integrate linguistic and non-linguistic elements, which contributed to their total multimodal literacy. The students perceived the teaching program positively, highlighting its engaging, motivating, and innovative aspects. They acknowledged the acquisition of valuable digital skills alongside enhanced English proficiency. The integration of technology was deemed crucial, aligning with the needs of the Industrial Revolution 4.0, and it significantly supported students' learning processes. The study concluded that multiliteracies pedagogy, when combined with technology, effectively fostered multimodal competence and prepared students for academic, personal, and professional success. These findings underscore the importance of incorporating multiliteracies approaches in English language teaching to address the evolving literacy landscape of the 21st century.